Improved water supply and water handling technologies: Revealed complements but perceived substitutes for safe water quality - Elena Groß; Isabel Guenther; Youdi Schipper (Development Engineering, 2022)
We analyze the impact of public water infrastructure and water handling technologies on the water quality and water handling behavior of households in rural Benin using both quasi-experimental and experimental household-level panel data. We find that the installation of improved village-level water sources induces households to reduce water disinfection efforts at home, indicating that households perceive improved public water infrastructure as a substitute for improved water handling to obtain safe drinking water. Consequently, point-of-use drinking water quality does not change. A reduction of contamination with E. coli at points of use can only be achieved if interventions providing drinking water technologies at the water source are complemented by household-level interventions and efforts to teach households how to maintain good water quality.
Keywords: D12; I38; O12; 330; Health; Quasi-experimental; RCT; Rigorous evidence; Water handling; Water quality; Water supply